2021
DOI: 10.3390/diagnostics11122181
|View full text |Cite
|
Sign up to set email alerts
|

Deep Learning Applications in Magnetic Resonance Imaging: Has the Future Become Present?

Abstract: Deep learning technologies and applications demonstrate one of the most important upcoming developments in radiology. The impact and influence of these technologies on image acquisition and reporting might change daily clinical practice. The aim of this review was to present current deep learning technologies, with a focus on magnetic resonance image reconstruction. The first part of this manuscript concentrates on the basic technical principles that are necessary for deep learning image reconstruction. The se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
17
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(28 citation statements)
references
References 51 publications
(70 reference statements)
1
17
1
1
Order By: Relevance
“…In recent years, new methods have been developed to reduce MRI acquisition time as well as the extent of artifacts and to achieve more precise imaging [ 4 , 5 , 6 ]. Recently, machine learning and artificial intelligence-based algorithms have found their way into clinical radiological imaging [ 7 , 8 ]. These deep learning algorithms (DL) are based on convolutional neural networks (CNN) that were developed on the basis of the function of animal neurobiology, resembling the human neural network [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, new methods have been developed to reduce MRI acquisition time as well as the extent of artifacts and to achieve more precise imaging [ 4 , 5 , 6 ]. Recently, machine learning and artificial intelligence-based algorithms have found their way into clinical radiological imaging [ 7 , 8 ]. These deep learning algorithms (DL) are based on convolutional neural networks (CNN) that were developed on the basis of the function of animal neurobiology, resembling the human neural network [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…The DL reconstruction provided improved image quality through the interplay of a PI model with a trained regularizer (in particular for higher accelerations), although a smoothing effect was observed in the images. 17 The conventional SNR measuring method based on 2 separate regions of interest from a single image, 25 one in the tissue of interest for signal intensity and the other in the background for noise, was inconsistent with the true SNR value obtained in accelerated imaging because the accelerating factor and phased-array coil systems could influence the noise distribution. 10,26,27 Methods to minimize this limitation by performing multiple acquisitions have been suggested in phantom studies, 10,11 although these methods are difficult to apply in practice.…”
Section: Discussionmentioning
confidence: 99%
“…The overall network typically comprises conventional data consistency steps (based on a signal model) interleaved with trainable regularization components. 16,17 A recently published study reported that DL with 3-fold PI maintained the image quality and diagnostic confidence of conventional 2-fold PI with remarkable acquisition time reduction in musculoskeletal TSE MRI. 16 In another study, DL-reconstructed 4-fold PI performed interchangeably with conventional PI in knee MRI 15 ; however, DL was applied only to PI with 3-or 4-fold acceleration, and the image quality was analyzed only subjectively.…”
mentioning
confidence: 94%
See 1 more Smart Citation
“…Due to lack of extensive real-world validation, however, there are no definitive data mandating their use in clinical practice to date [ 36 ]. Despite interesting results from earliest reports of AI implementations focusing on automated detection and characterization of PCa, currently there is increasing interest for using AI technology to improve quality control and workflow efficiency in radiology [ 37 ].…”
Section: Discussionmentioning
confidence: 99%